METHODS OF TEACHING FOREIGN LANGUAGES USING DIGITAL TECHNOLOGIES (Proceedings of International Educators Conference, 2023)
A foreign language is a language that is not the native language of people. A person can learn a foreign language only by studying - in schools, language courses and self-taught ways l - or through playing as a child living in a foreign language area. It is important to know at least one foreign language at work and anywhere.